LEVEL OF INTERLEUKIN-6 IN OBESE PEOPLE WITH AND WITHOUT INSULIN RESISTANCE - Nedya Safitri; Bambang Sigit Riyanto; H. Ahmad Husain Asdie (Faculty of Medicine Universitas Gadjah Mada, 2011)
ABSTRACTBackground. Obesity is one of the risk factor for type 2 diabetes mellitus characterized by insulin resistance, decrease insulin secretion and hyperglycemia. Chronic inflammation has been proposed to have an important role in the pathogenesis of obesity related insulin resistance. A number of studies have indicated that several humoral markers of inflammation are elevated in people with obesity and type 2 diabetes mellitus, because adipose tissue secretes a number of proinflammatory cytokines, including interleukin-6. The level of plasma IL-6 is increase in obese people.Objective. To investigate the mean of difference in the level of IL-6 in obese people with and without insulin resistance.Subjects and Method. The study design was cross-sectional. It was conducted in obese people with BMI ≥ 25 kg/m2. Insulin resistance were measured with HOMA-IR methode, calculated using the following formula: fasting serum glucose X fasting plasma insulin/22,5. Insulin resistance was defined when HOMA-IR > 2,77. Interlukin-6 was measured with Quantikine High Sensitivity human IL-6 ELISA. Difference of mean of IL-6 level was analyzed by student’s t-test for normal distribution and Mann- Whitney U-test if distribution was not normal.Results. There were 56 subjects, 24 (42,9%) subjects with insulin resistance and 32 (57,1%) subjects without insulin resistance. Obese people with insulin resistance had higher mean level of IL-6 than obese people without insulin resistance, although the difference was not significant (20,05±8,59 vs 18,98±8,15 pg/ml; p=0,639; 95% CI -5,58-3,46).Conclusion. There was no difference in the mean of IL-6 level in obese people with and without insulin resistance. Keywords. IL-6, obese, insulin resistance